Study on microstructure and properties evolution of duplex stainless steel powders by high-energy ball milling - Wenqing Sheng; Jingkun Li; Binguo Fu; Tianshun Dong; Guolu Li; Shengjun Ma; Haipeng Shao; Zhiwei Niu (Journal of Materials Research and Technology)
Powder metallurgy duplex stainless steels have garnered significant attention due to its exceptional mechanical properties. The preparation of raw material powders plays a crucial role in the sintering process of duplex stainless steels. The effects of high-energy ball milling on microstructure and properties of duplex stainless steel powders have been studied. Results show that the particles size are effectively reduced by increasing the rotation speed. After milling at 800 r/min for 15 h, the particles size of duplex stainless steel were reduced from 86.17 μm to 69.46 μm and the α and γ phases were uniformly distributed. Additionally, the microstructure of sintered duplex stainless steel milled at 800 r/min is refined and the microhardness is increased from 267 HV0.3 to 313 HV0.3, with improvement of 17.23%, which is attributed to the grain refinement through high-energy ball milling.